Typification of the names Epilobium lanceolatum, Lotus requienii, Orchis romana, and Romulea columnae described from Rome (Italy) - Iamonico, Duilio; Millozza, Anna; Iberite, Mauro (Phytotaxa, 2020)
The names Epilobium lanceolatum, Lotus requienii (currently accepted as Lotus conjugatus subsp. requienii), Orchis romana (currently accepted as Dactylorhiza romana subsp. romana), and Romulea columnae are lectotypified on specimens kept at RO and BOLO, and on a Sebastiani’s illustration published in his Romanarum plantarum fasciculus primus. An epitype (at RO) for the name Epilobium lanceolatum is also designated.